Microstructural adjustment of hot-rolled Ti–6Al–4V based on a CCT diagram. Issue 13 (2nd September 2022) - Janda, Alexander; Ebenbauer, Stefan; Prestl, Aude; Siller, Ingo; Clemens, Helmut
Abstract : The effects of post-processing heat treatments on hot-rolled Ti–6Al–4V with extra low interstitial concentration were investigated. The 2 mm sheets were rolled in the single β phase field region and subsequently cooled in air. A continuous cooling transformation (CCT) diagram was generated, revealing the strong influence of the cooling rate on both microstructure and hardness. Cooling rates between 0.01 and 200°C s −1 were selected. While rapid cooling resulted in a martensitic transformation β → α′, a decrease in the cooling rate led to a progressive spheroidization of the lamellar (α + β) microstructure. With a focus on the established CCT continuous cooling transformation diagram, this study contains insight on the microstructure evolution of the Ti–6Al–4V ELI alloy during cooling from the single β phase field region.